2015
DOI: 10.1159/000441777
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Determinants of Cannabis Dependence: A Systematic Review of the Literature

Abstract: Background: Many studies have examined factors associated with the first onset of cannabis use and abuse. Currently, there is relatively little research regarding conditions under which cannabis dependence is more likely to emerge. Although previous studies have examined different potential determinants of cannabis dependence, to our knowledge, a systematic review is lacking. Aims: The study aims to identify recent findings regarding psychosocial determinants of cannabis dependence and to summarize them system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 66 publications
(119 reference statements)
2
36
3
Order By: Relevance
“…However, similar to these prior cross-sectional studies, we found positive relationships between social, enhancement, and coping motives and quantity. Although these and other prior studies show higher motives are positively associated with cannabis consumption, severity, and psychosocial outcomes (e.g., anxiety, depression; not measured in the current analyses) at broader levels of measurement (Benschop et al, 2015; Bonn-Miller and Zvolensky, 2009b; Schlossarek et al, 2016; Simons et al, 1998; Zvolensky et al, 2007), this is one of the first studies to examine acute same-day relationships between cannabis motives and quantity.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, similar to these prior cross-sectional studies, we found positive relationships between social, enhancement, and coping motives and quantity. Although these and other prior studies show higher motives are positively associated with cannabis consumption, severity, and psychosocial outcomes (e.g., anxiety, depression; not measured in the current analyses) at broader levels of measurement (Benschop et al, 2015; Bonn-Miller and Zvolensky, 2009b; Schlossarek et al, 2016; Simons et al, 1998; Zvolensky et al, 2007), this is one of the first studies to examine acute same-day relationships between cannabis motives and quantity.…”
Section: Discussioncontrasting
confidence: 53%
“…Although many factors across levels of social ecology influence substance use (Abadi et al, 2011; Keyes et al, 2011; Sallis et al, 2008; Tang and Orwin, 2009), motives (i.e., reasons for use) are an important individual-level characteristic because they are related to negative consequences (Blevins et al, 2016b; Lee et al, 2009), including developing cannabis use disorders (Benschop et al, 2015; Schlossarek et al, 2016). Motives may change as a result of cannabis interventions; in prior work, reductions in motives (particularly coping-related motives) predicted post-intervention reductions in consumption and consequences (Blevins et al, 2016a), underscoring the need to examine how cannabis-related motives affect consumption.…”
Section: Introductionmentioning
confidence: 99%
“…But the heterogeneity of populations and study designs makes it difficult to conduct proper systematic reviews or meta-analyses at this point in time. In one of its main conclusions, a just-completed and very ambitious systematic review on the topic of cannabis use and cannabis dependence illustrates the complex challenges faced when trying to forge chains of inference from heterogeneous sources of evidence: “…, the link between cannabis dependence and predisposing factors could not be resolved convincingly by most studies due to methodological weaknesses regarding dependence criteria [49]. …”
Section: The Five Main Rubrics Of Epidemiology As Applied To Cannabismentioning
confidence: 99%
“…Some reports indicate the potential value of cannabis for therapeutic purposes (CTP) [10–15]. However, some concerns around the addictive potential of cannabis are evident [4, 5, 16] but with a weak evidence base indicating lower probability of dependence and physical and social harm when compared to alcohol, cocaine, opiates and nicotine [4]. Legalisation in the form of de facto legal supply for medical use (CTP) does not appear to have created a significant threat to public health and safety, or caused increased consumption or related harms [1720].…”
Section: Introductionmentioning
confidence: 99%